Resilience as a Key Factor in the Success of Women-Led Entrepreneurship: A Systematic Literature Review - Feria Hernandez, Melissa Dalila (2024)
Resilience in female entrepreneurship emerges as a critical component that significantly influences the achievement and capacity to overcome challenges inherent in the creation and management of businesses. To address this topic, the present article focused on conducting a systematic review of the scientific literature to examine how resilience stands as a determining factor enabling female entrepreneurs to navigate obstacles and achieve success in their ventures. In line with this objective, a bibliographic methodology was implemented that included synthesizing information from various databases, including Scopus, Web of Science, and SciELO. The results reveal a scarcity of publications on this particular topic, thus highlighting the importance of addressing these gaps in the literature. This approach is essential for gaining a more holistic understanding of the relationship between resilience and female entrepreneurship in various contexts. In this sense, the 152 articles analyzed during the research constitute a valuable starting point for future investigations, evidencing the need to delve deeper into the analysis of resilience in the context of female entrepreneurship. Identifying and understanding these gaps in the scientific literature not only enriches the existing knowledge but also guides new research directions that contribute to the advancement and consolidation of this field of study. Consequently, resilience in female entrepreneurship not only acts as a driver for overcoming challenges but also plays a crucial role in building a more equitable and diverse business environment. The scientific evidence found during the systematic literature review is considered an essential component of promoting gender equality and diversity in the business sphere. In the abovementioned review, the relevance of factors such as resilience, self-efficacy, and support networks in the realm of female entrepreneurship is highlighted. These studies provide valuable perspectives that not only enrich existing knowledge but can also guide the development of policies and practices aimed at creating a more inclusive and equitable environment for female entrepreneurs. The interconnection between these elements underscores the importance of considering not only individual resilience but also the impact of external factors and support in fostering a more favorable business ecosystem for women.